Railroad Turnouts – From Surveying to Information System - Hodas, Stanislav (Communications - Scientific letters of the University of Zilina, 2000)
Railroad turnouts and crossings are inseparable elements of railway infrastructure for providing the fluent train traffic which are as a rule, joined into certain trackage groups. The information registration of their position in the railway lay-out is necessary. In our case we will point out the design of the information system which could be employed in the railway engineering works during the maintenance of the above mentioned objects in operation. This information system was created for the independent railway society which owns the railway yard in its railway system.